1998
DOI: 10.1111/j.1439-0450.1998.tb00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tylosin Tartrate on Humoral Immune Responses in Chickens

Abstract: While many antimicrobial agents have been reported to cause immunosuppression in animals, macrolide antibiotics enhance the immune function. Tylosin tartrate is a macrolide antibiotic approved for the control of mycoplasmosis in poultry. The purpose of this investigation was to determine the effect of tylosin on the humoral immune functions in chickens. Three days after oral tylosin tartrate administration, 4-or 8-week-old chickens were immunized intravenously with carbolic acid-killed Brrcce/la abortus bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
4
1
Order By: Relevance
“…This result is not surprising given that vaccination against coccidiosis can induce robust humoral and cell-mediated immunities in broiler chickens (Jang et al, 2011). However, we failed to see anticoccidials-altered splenocyte proliferation, which is contrary to the previous studies (Baba et al, 1998;Munir et al, 2009) in which antibiotic or anticoccidial treatment exhibited increased mitogen-stimulated proliferation compared with the controls. It cannot be excluded the possibility that chickens treated with anticoccidials for 7 days may not be enough to see the effects on splenocyte proliferation.…”
Section: Serological Monitoring Of Serum Antibody Titers Against Ibvcontrasting
confidence: 80%
See 1 more Smart Citation
“…This result is not surprising given that vaccination against coccidiosis can induce robust humoral and cell-mediated immunities in broiler chickens (Jang et al, 2011). However, we failed to see anticoccidials-altered splenocyte proliferation, which is contrary to the previous studies (Baba et al, 1998;Munir et al, 2009) in which antibiotic or anticoccidial treatment exhibited increased mitogen-stimulated proliferation compared with the controls. It cannot be excluded the possibility that chickens treated with anticoccidials for 7 days may not be enough to see the effects on splenocyte proliferation.…”
Section: Serological Monitoring Of Serum Antibody Titers Against Ibvcontrasting
confidence: 80%
“…Thus, further studies are warranted to address the concern raised in this study. (Baba et al, 1998). In a study by Arias and Koutsos (2006), they reported that antibiotic-fed chickens raised on fresh litter had higher duodenal lymphocytes, but lower ileal lymphocytes compared with non-medicated control chickens.…”
Section: Serological Monitoring Of Serum Antibody Titers Against Ibvmentioning
confidence: 99%
“…For example, tylosin showed moderate effects on the splenocyte proliferation, splenocyte conditioned medium proliferative activity, and splenocyte anti-tumour activity in chicken (Baba et al 1998a). It has also been reported that tylosin has an effect on increasing the antibody production and can modulate the number of antibody producing cells in chickens (Baba et al 1998b). In a study, male rats treated with tylosin (0.1 and 5.0 mg tylosin/kg feed) for three different periods 15, 29 and 65 days, showed reduced levels of the luteinizing hormone (LH) and the follicle stimulating hormone (FSH) in the pituitary gland (Meisel et al 1993a).…”
mentioning
confidence: 99%
“…Azithromycin and toltrazuril have different mechanisms of action (Baba et al 1998;Gottstein et al 2001;Davis et al 2002;Dirikolu et al 2009). Thus, we also tried a combination of azithromycin and toltrazuril as a treatment option.…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin, an azalide antibiotic, is similar to the macrolides, which exhibit immunemodulating effects, including a strengthening of humoral and cellular immune responses, a reduction in the production of inflammatory mediators and an increase in the production of Interleukin 10. The macrolide antibiotics also exhibit anti-inflammatory effects which include dramatic induction of COX-2 gene expression and of nitrite oxide synthases (Baba et al 1998). Studies conducted in numerous species have, taken together, demonstrated that azithromycin has good oral bioavailability and exhibits an extensive tissue distribution with very slow elimination; thus, it exerts a prolonged anti-bacterial effect at the site of action.…”
mentioning
confidence: 99%